The Influence of Brand Image, Product Quality, and Price on Purchase Decisions : Study on iPhone Smartphone Users in Malang City - Rianty Astrid Pratiwi; Ratih Juliati; Chalimatuz Sa'diyah (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
The purpose of this study is to test and analyze the effect of brand image, product quality, and price on purchasing decisions. The population in this study was the overall student of iPhone smartphone users in Malang city with a sample of 128 respondents. The characteristics of respondents are students located in the city of Malang and students who first bought the iPhone brand smartphone. Sampling techniques use snowball sampling. The study was conducted in June 2021 using an online questionnaire. Data analysis techniques are performed using multiple linear regressions. The results of this study concluded that brand image, product quality, and price have a positive and significant effect on purchasing decisions. The quality of the dominant product influences the purchase decision because smartphone consumers prioritize the advantages possessed by iPhone smartphone products